Analysis of the Causality Links between the Growth of the Construction Industry and the Growth of the Nigerian Economy - Abubakar, Mu'awiya; Abdullahi, Muhammad; Bala, Kabir (Penerbit Universiti Sains Malaysia, 2018)
The construction industry makes a signifcant contribution to the growth and development of every economy, by providing infrastructure for other productive ventures, shelter to the citizens and generating employment to people of different levels of knowledge and skills. In Nigeria, the construction industry contributes an average of over 3% to the annual gross domestic product and an average of about one-third of the total fxed capital investment. Despite the huge potentials of the Nigerian construction industry, little attention is given to its signifcance in driving the Nigerian economy to greater heights. This study explored the empirical evidence of causal relationship between the growth and development of the Nigerian economy and that of the construction sector. Econometric techniques such as unit root test, Granger causality test and Johansen's co-integration test were conducted to establish the actual relationship between the output of the construction sector (CS) and the gross domestic product (GDP) of the country. Twenty six years' time series data for the CS and the GDP between 1990 to 2015 was obtained from the statistics database of the Central Bank of Nigeria (CBN) and used for the analyses. The research revealed that despite the harsh economic realities facing the country in recent times, there exist a bi-directional linkage between the CS and the GDP of Nigeria. Each of them precedes the other by one year. The study recommends that any effort to diversify the Nigerian economy should consider revamping the construction industry for improved productivity in order to beneft from its signifcant positive effects on the economy.